NO and performance characteristics of a CI engine operated on emulsified fuel - Okumus, Fatih; Kokkulunk, Gorkem; Gonca, Gueven; Kaya, Ibrahim (INDERSCIENCE ENTERPRISES LTD, 2023)
Emulsified fuels are among the alternative solutions nowadays when global warming and emissions are on the hot topic. This research presents the experimental and computational results of an engine running on emulsified fuel containing 10% water. The investigated engine in experiments is a naturally aspirated, single-cylinder diesel engine. In-cylinder pressure, power output, specific fuel consumption and NO emission data have been obtained from experiments and this data have been used to fit some coefficients of the two-zone combustion model. After fitting the coefficients, the effect of design parameters, bore, stroke, inlet pressure and temperature, compression ratio, equivalence ratio, residual gas fraction, cylinder wall temperature, and start of injection time, on engine performance have been investigated. As a result, the largest reductions in NOx emissions were 91.28% and 88.21% at 15% and 15?A greater crank angles than the original values for residual gas fraction and ignition time, respectively.
Keywords: engine design; emulsified fuel; water-diesel emulsion; NO emissions; combustion model; engine combustion; model-based calibration; compression ratio; equivalence ratio; residual gas fraction; injection time; inlet pressure; inlet temperature; cylinder wall temperature; COMBUSTION CHARACTERISTICS; DESIGN PARAMETERS; DIESEL-ENGINE; DUAL-FUEL; EMISSIONS; Environmental Sciences & Ecology